Full probabilistic service life prediction and life cycle assessment of concrete with fly ash and blast-furnace slag in a submerged marine environment: a parameter study. (1st January 2012) - Van den Heede, Philip; Maes, Mathias; Gruyaert, Elke; De Belie, Nele
Nowadays, more attention is being paid to sustainability in construction. Over the years, the concrete research community has developed a wide range of potential 'green' concretes. To reduce cement related CO2 emissions, a considerable part of the traditional binder can be replaced with industrial by-products. However, as a result of the current focus on comparative durability assessment based on accelerated tests, sufficient knowledge on the actual service life and sustainability of these materials is still lacking. In this paper, we combined both approaches for concrete exposed to chlorides. Different mixes were subjected to a rapid chloride migration test. With the results obtained, probabilistic service life prediction was done. This service life together with the material's strength was used as input for life cycle assessment of an axially loaded column. Results show that the environmental impact of fly ash and slag concrete is less than half the impact of traditional concrete.